Unconventional Hanle effect in a highly ordered CoFe/MgO/n-Si contact: non-monotonic bias and temperature dependence and sign inversion of the spin signal - Jeon, Kun-Rok; Min, Byoung-Chul; Shin, Il-Jae; Park, Chang-Yup; Lee, Hun-Sung; Jo, Young-Hun; Shin, Sung-Chul (IOP PUBLISHING LTD, 2012)
We report in this paper the unconventional bias and temperature dependence of the Hanle effect in a highly ordered CoFe/MgO/n-Si contact investigated by means of a three-terminal Hanle method. The spin signal and the effective spin lifetime obtained in this system show non-monotonic behavior with bias and temperature variations. Interestingly, the sign of the spin signal changes significantly with the bias voltage at a low temperature. The sign inversion is presumably ascribed to the contribution of interfacial resonant states formed at the CoFe/MgO interface or bound states in the Si surface during the spin extraction process.